STANDAR KELENGKAPAN ALAT RESTAURANT PETERSELI PEKANBARU - Disa Islamey. N; Andi Moh Rifiyan Arief (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
This research aims to determine about to find standard completeness equipment for Peterseli restaurant Pekanbaru. Standard completeness equipment is a measuring instrument used and already available or complete, so with completeness amenities all activities carried out. Without complete equipment it will inhibit company activities and objectives will not be achieved. This research to make use qualitative method to analysis set of case, wich to become the key informan in this research as much as three people’s. That is 1 Owner, 1 Manager and 1 Chef. Sources were obtained through observation, interview and documentation. Based on result of this research, the conclusions of this research are standard completeness equipment for restaurant in accordance with the stadards, but still needs to be improved raising required so that Peterseli Restaurant Pekanbaru will be better in the future. Keywords : Standard, Completeness Equipment, Restaurant